2020
DOI: 10.1021/jacs.0c08262
|View full text |Cite
|
Sign up to set email alerts
|

C2-Symmetric Dinickel Catalysts for Enantioselective [4 + 1]-Cycloadditions

Abstract: Dinickel naphthyridine−bis(oxazoline) catalysts promote enantioselective intermolecular [4 + 1]-cycloadditions of vinylidene equivalents and 1,3-dienes. The products of this reaction are methylenecyclopentenes, and the exocyclic alkene is generally obtained with high Z selectivity. E-and Z-dienes react in a stereoconvergent fashion, providing cycloadducts with the same sense of absolute stereochemistry and nearly identical ee values. This feature allows dienes that are commercially available as E/Z mixtures to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 49 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…52 We found that chiral napthyridine−bis(oxazoline) ligands (napbox) could be prepared and subsequently metalated to form (napbox)Ni 2 (OAc) complexes. 53 Complex 21 is an effective catalyst for enantioselective, intermolecular [4 + 1]-cycloaddition reactions, providing ee values of up to 98%.…”
Section: Vinylidene Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…52 We found that chiral napthyridine−bis(oxazoline) ligands (napbox) could be prepared and subsequently metalated to form (napbox)Ni 2 (OAc) complexes. 53 Complex 21 is an effective catalyst for enantioselective, intermolecular [4 + 1]-cycloaddition reactions, providing ee values of up to 98%.…”
Section: Vinylidene Transfermentioning
confidence: 99%
“…Substituted oxazolines are commonly used in chiral ligands for asymmetric catalysis but have not been widely incorporated into binucleating ligand frameworks (Figure C) . We found that chiral napthyridine–bis­(oxazoline) ligands (napbox) could be prepared and subsequently metalated to form (napbox)­Ni 2 (OAc) complexes . Complex 21 is an effective catalyst for enantioselective, intermolecular [4 + 1]-cycloaddition reactions, providing ee values of up to 98%.…”
Section: Stoichiometric Reactivity and Catalysismentioning
confidence: 99%
“…To complete the coordination sphere of the nickels, a benzene was introduced as a π-bridging ligand (Figure I.4a). 36 This specific complexes can promote a large variety of cyclisations [37][38][39][40][41][42][43] like alkyne cyclotrimerisation, [4+1] cycloaddition of diene, cyclopropanation and the Pauson-Khand reaction. The groups of Bera 44 and Tilley, 45 45 In naphthyridine complexes, the C-H reaction can occur on the naphthyridine ligand itself or on another reactant coordinated to the metal(s).…”
Section: -Introduction 1 -Naphthyridine Based Complexesmentioning
confidence: 99%
“…Moreover, distinct formal (3+2) cycloadditions which have also been useful for the construction of enantioriched cyclopentenes derivatives employed N-heterocyclic carbene (NHC)-catalyzed reactions, [20][21][22] metal carbenoids, 23 and the ring opening of cyclopropanes. [24][25][26] Although less explored, formal (4+1) cycloaddition is also a suitable strategy and, according to the recent literature, [27][28][29] either phosphine 30 and metal-catalyzed 31 are versatile and powerful approaches for the construction of these five membered ring systems. In 2014, Fu and co-workers disclosed a biphenyl phosphine-catalyzed enantioselective (4+1) annulation of allenoates with Michael donors (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Although less explored, formal (4 + 1) cycloaddition is also a suitable strategy and, according to recent literature, 27–29 phosphine 30 and metal catalysis 31 are versatile and powerful approaches for the construction of these five membered ring systems. In 2014, Fu and co-workers disclosed a biphenyl phosphine-catalyzed enantioselective (4 + 1) annulation of allenoates with Michael donors ( Scheme 1b ).…”
Section: Introductionmentioning
confidence: 99%